2022
DOI: 10.1002/jia2.26047
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome among treatment‐naïve people living with and without HIV in Zambia and Zimbabwe: a cross‐sectional analysis

Abstract: Introduction Chronic viral replication has been linked to an increased risk of cardiovascular and metabolic diseases in people living with HIV (PLWH), but few studies have evaluated this association in Southern Africa. We explored the determinants of metabolic syndrome (MetS) among treatment‐naïve adults living with and without HIV in Southern Africa. Methods Treatment‐naïve PLWH and people living without HIV (PLWOH) ≥30 years were consecutively enrolled from primary ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…From November 2020 to July 2021, we conducted an exploratory qualitative study with participants from a Clinic and a 1st Level Hospital, both characterized by a high HIV burden (>10,000 PLWH) and enrolled in the International Epidemiology Databases to Evaluate AIDS collaboration in Southern Africa (IeDEA-SA) study [ 20 ]. Ethical approval was provided by the University of Zambia Biomedical Research Ethics Committee (UNZABREC)-approval number 011-04-19.…”
Section: Methodsmentioning
confidence: 99%
“…From November 2020 to July 2021, we conducted an exploratory qualitative study with participants from a Clinic and a 1st Level Hospital, both characterized by a high HIV burden (>10,000 PLWH) and enrolled in the International Epidemiology Databases to Evaluate AIDS collaboration in Southern Africa (IeDEA-SA) study [ 20 ]. Ethical approval was provided by the University of Zambia Biomedical Research Ethics Committee (UNZABREC)-approval number 011-04-19.…”
Section: Methodsmentioning
confidence: 99%
“…Among the 25 included studies, eight were from Ethiopia [21][22][23][24][25][26][27][28] , six were from South Africa [29][30][31][32][33][34] , three were from Nigeria [35][36][37] , two were from Kenya 38,39 , two were from Zambia 40,41 , and one each was from Cameroon 42 , Uganda 43 , Botswana 44 , and Zimbabwe 40 . The included study sample sizes ranged from 79 45 to 1108 41 , with a total of 8602 people living with HIV/AIDS.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Twenty-two studies reported impaired fasting glucose and Low HDL levels 22,24,26,[28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][46][47][48] , 24 studies reported high triglyceride levels, and 20 studies reported hypertension/raised BP and increased waist circumference/ abdominal obesity 21,22,[24][25][26][27][28][29]31,32,34,35,[37][38][39][40][41][42]44,45,48…”
Section: Sub-components Of Metabolic Syndromementioning
confidence: 99%